The Role Of Collaborative Governance In Indonesian Disaster Management - Khafian, Nidaan (Journal of Governance and Administrative Reform, 2023)
Abstract Natural and non-natural disasters are unavoidable in Indonesia because the country's geographical area causes it to be threatened with floods, earthquakes, volcanoes, and tsunamis. Therefore, this study aims to determine the importance of collaborative governance in disaster management. This study used a qualitative approach with literature methods and secondary data to explore the role of collaborative governance in Indonesian disaster management. The results showed that all emergency mitigation requires coordination between government and non-government agencies. Meanwhile, the pre-disaster as one of the disaster management phase enable collaborative governance to create a disaster-resilient community, while the post-disaster is performed by applying a community-based recovery approach and assistance cooperation. Furthermore, weak coordination and leadership are factors affecting the collaboration process. Keywords: natural disasters, collaborative governance, disaster management, pre disaster, post disaster Abstrak Bencana alam dan non-alam tidak dapat dihindari di Indonesia karena kondisi geografis negara yang menyebabkannya terancam oleh banjir, gempa bumi, gunung berapi, dan tsunami. Oleh karena itu, penelitian ini bertujuan untuk mengetahui pentingnya tata kelola kolaboratif dalam penanggulangan bencana. Penelitian ini menggunakan pendekatan kualitatif dengan metode literatur dan data sekunder untuk mengeksplorasi peran tata kelola kolaboratif dalam penanggulangan bencana di Indonesia. Hasil penelitian menunjukkan bahwa semua mitigasi darurat memerlukan koordinasi antara lembaga pemerintah dan non-pemerintah. Sementara itu, prabencana sebagai salah satu tahapan penanggulangan bencana memungkinkan tata kelola kolaboratif untuk mewujudkan masyarakat tangguh bencana, sedangkan pascabencana dilakukan dengan menerapkan pendekatan pemulihan berbasis komunitas dan kerja sama bantuan. Selain itu, lemahnya koordinasi dan kepemimpinan menjadi faktor yang mempengaruhi proses kolaborasi. Kata kunci: bencana alam, tata kelola kolaboratif, manajemen bencana, pra bencana, pasca bencana